A Young Boy with Painful Eye Swelling and Facial Rash - Mahbub, Md Shahriar; Al Faruq, Abdullah; Siddiqui, Md Mahmudur Rahman; Khan, Mohammad Ashik Imran; Ahasan, HAM Nazmul; Alam, Md Billal; Miah, Md Titu; Gupta, Ratan Das (Journal of Medicine, 2011)
Oculomotor palsy is a recognized uncommon complication in herpes zoster ophthalmicus. A case of herpes zoster ophthalmicus with ophthalmoplegia is reported. A 15 year old boy presented with ptosis, chemosis, proptosis, ophthalmoplegia involving IVth and VIth cranial nerve following vesicular eruption on his right forehead. He was treated with oral acyclovir and oral steroids. He made a partial recovery with improvement of ptosis, proptosis but with residual VIth nerve palsy. Keyword: Herpes zoster ophthalmicus; ocular herpes zoster; ophthalmoplegia; Bangladesh DOI: 10.3329/jom.v12i1.6938 J Medicine 2011; 12 : 91-93